2016
DOI: 10.1186/s11671-016-1733-x
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed Hybrid Light-Emitting Devices Comprising TiO2 Nanorods and WO3 Layers as Carrier-Transporting Layers

Abstract: The goal of this research is to prepare inverted light-emitting devices with improved performance by combining titanium dioxide (TiO2) nanorods and tungsten trioxide (WO3) layer. TiO2 nanorods with different lengths were established directly on the fluorine-doped tin oxide (FTO) substrates by the hydrothermal method. The prepared TiO2 nanorods with lengths shorter than 200 nm possess transmittance higher than 80% in the visible range. Inverted light-emitting devices with the configuration of FTO/TiO2 nanorods/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The TiO 2 exhibits an average transmittance of 98% in the visible region from 500 to 700 nm, while TPBi shows the average transmittance of 86% in the visible region. This reduction in absorbance and enhancement of transmittance may be attributed to the good morphology of the film and the optical properties of the materials. , Moreover, the doped ETL used in the study exhibits excellent transmittance up to 700 nm, which makes it a valuable option for use in highly efficient OLED applications.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The TiO 2 exhibits an average transmittance of 98% in the visible region from 500 to 700 nm, while TPBi shows the average transmittance of 86% in the visible region. This reduction in absorbance and enhancement of transmittance may be attributed to the good morphology of the film and the optical properties of the materials. , Moreover, the doped ETL used in the study exhibits excellent transmittance up to 700 nm, which makes it a valuable option for use in highly efficient OLED applications.…”
Section: Resultsmentioning
confidence: 91%
“…These metal oxides have significant potential to enhance the performance of OLEDs owing to superior properties such as excellent carrier mobility, hole-blocking capability, and stability in air. Vasilopoulou et al demonstrated ZrO 2 ETL-based OLED by the atomic layer deposition method and enhanced the performance of the OLED. , Tsai et al demonstrated TiO 2 and WO 3 as ETMs introduced in OLED and achieved a maximum luminance of 4493 cd m –2 and CE of 0.66 cdA –1 for TiO 2 nanorod-based devices . Jia et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific nanostructures of the above three materials can be grown via the hydrothermal method, and the growth temperature of ZnO is the lowest among the three oxides. For example, TiO 2 or WO x nanorods can be grown on the substrate from their precursor solutions at 170 °C with the aid of Teflon-lined autoclaves [ 8 , 9 ], while ZnO nanorods are easier to grow on the substrate at a lower temperature of 95 °C [ 10 ]. Besides, ZnO possesses many fascinating properties, including earth abundance, non-toxicity, high transmittance in the visible range, and large piezoelectric response [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%